An electrooptic chaotic system based on a hybrid feedback loop - Cheng, Mengfan (2020)
An electrooptic chaos source is proposed based on phase-modulation-to-intensity-modulation conversion theory and an analog-digital hybrid time-delay feedback loop. The analog part takes the digital binary sequences from shift registers as input and converts them into an analog noise-like signal, from which new bits are determined. The dynamical characteristic of the generated waveform is studied in detail by means of spectrum analysis, periodicity analysis, correlation performance, and complexity analysis. Moreover, the evolution between chaos and stochastic noise is observed and measured by adopting the complexity-entropy curves when a random perturbation is introduced. Such a perturbation can help with recovering chaotic dynamics from degradation. Based on this chaotic source, a secure and robust synchronization scheme that can exactly reproduce the signal is put forward. The effect of parameters' mismatch and noise level on the synchronization quality is also investigated. The scheme has the potential to be applied in various applications when a robust random source is needed.